Effect of different arrangements of point source, aluminum absorber and detector on mass absorption coefficient of beta-particles - Gurler, Orhan; Yalcun, S. (Springer Science and Business Media LLC, 2005)
The transmission of 0.766 MeV beta-particles emitted from 204Tl through aluminum has been investigated for different arrangements of point source, absorber and detector. In the first arrangement, the mass absorption coefficient (μm) has been measured as a function of the absorber to the source distance (HAS), when the absorber foil was placed just above the window of a surface barrier solid state detector. In the second arrangement, the mass absorption coefficient has been measured as a function of the absorber to detector distance (HAD), when the absorber foil was placed just on the source. The measured mass absorption coefficients of beta-particles have been compared to the values gained in a previous work.